Oracle parallel processing - Mahapatra, Tushar (O'Reilly, 2000)
"Oracle Parallel Processing is the first book to describe the full range of parallel processing capabilities in the Oracle environment, including those new to Oracle8i." "Oracle Parallel Processing also contains several case studies showing how you might use Oracle's parallel features in a variety of real-world situations."--Jacket